Music Matters: Diplomasi Budaya Indonesia terhadap Negara di Kawasan Pasifik Melalui ‘the Symphony of Friendship’ di Selandia Baru - Bernadette, Sophia; Septiana, Rizka; Kusumawardhana, Indra (Universitas Diponegoro, 2022)
This study aims to determine Indonesia's strategy in implementing cultural diplomacy and soft power diplomacy through the cultural event ‘The Symphony of Friendship’ by the Indonesian Embassy in New Zealand. Using a descriptive qualitative research method with data collection techniques through semi-structured in-depth interviews, which are then analyzed in depth supported by trust checking techniques through triangulation of data sources. The findings in this study are cultural diplomacy aimed at building Indonesia's image in the South Pacific region in dealing with separatist issues in Papua, which have been raised internationally by several countries, namely Fiji, Solomon Islands, Vanuatu and Papua New Guinea. The TSF was conducted to build a perception of Indonesia in the Pacific community as a colonialist against Papua, presenting a positive perception so that Indonesia is not seen as carrying out repression in Papua through a cultural approach and embracing the community to work together and encourage togetherness through a musical approach.